QUALITY OF HOSPITAL CARE IN THE DELIVERY AND POSTPARTUM AREA OF TEOFIL DÁVILA GENERAL HOSPITAL - Morales, Vicky Narea; Nader, Jorge Daher; Rodríguez, Katherine; Jimenez, Gabriel; Bath, Cynthia Armijos (International Journal of Research -GRANTHAALAYAH, 2020)
The quality of care in hospital services indicates that it is a matter of academic debate as there are various approaches to its measurement, control and monitoring. The objective is to evaluate the quality of hospital care, analyzing the satisfaction of mothers during the prepartum, delivery and postpartum period at the Teófilo Dávila General Hospital in Machala. The sample was of 200 patients from the area of Gynecology - Obstetrics. The study covers the period between March - August 2019. The research is descriptive, not experimental, it was cross-sectional, since the data were taken only once; the investigation technique was the survey and observation, the instrument that was used was the questionnaire. As a result, it is evident that 95% of the respondents give a 9/10 rating to the quality of care during delivery, 83% give a rating of 9 during the delivery care. And it is shown that the satisfaction of the patients who were attended and surveyed was 80%, understood to be satisfied during the delivery stage and 76% during the postpartum period. In conclusion, the Gyneco-Obstetrics service of Teófilo Dávila - Machala General Hospital was globally evaluated as a good quality service. The majority of patients perceive the care received as satisfactory, the study constitutes the quality of care provided by the obstetric center, taking into account each of the preparatory, childbirth and postpartum stages.